Molecular Theory Investigates the Switching of Mixed Brushes (Journal of Atomic and Molecular Sciences, 2014)
We performed a molecular theory to study the switching mechanism ofmixed brushes. For mixed brushes, because of the different solvent selectivity, onespecies forms the poor solvent layers, whereas another species creates the upper, goodsolvent layer. The structural properties of the mixed brushes were analyzed in detailfor various solvent responds. The thermodynamic properties of the mixed brushes,such as the lateral pressure-area isotherms and chemical potentials, are studied as afunction of surface coverage. The possibility of perpendicular segregation in mixedbrushes is explained. The presented results allow us to quantify the responsive featuresof mixed brushes and provide guidance for the design of multicomponent brushesfor specific applications.
Keywords: mixed brushes; molecular theory; perpendicular segregation.